How and Why the Gender Pension Gap in Urban China Decreased between 1988 and 2018 - Björn Anders Gustafsson; Peng Zhang; Hanrui Jia (Institute of Labor Economics (IZA), 2023)
In urban China, gender gaps in employment and earnings have steadily increased since the 1990s. Such gender gaps are important because pension rights and amounts are based on labor force participation and wages. However, as this study demonstrates, despite the rise in gender differences in the urban labor market, the average gender pension gap decreased between 1988 and 2018. In the paper, we describe the evolution of the fragmented pension system in urban China using a quantitative approach that distinguishes between pension coverage rates and average benefit amounts. Additionally, we conducted a birth cohort analysis to gain further insights into the reasons for changes in the gender pension gap. We utilized data from the China Household Income Project, focusing on individuals aged 60 years and older. Therefore, this study demonstrates how changes in China's pension system have benefited women more than men during the aforementioned period.
Keywords: H55; J14; J26; P36; 330; gender pension gap; pension reforms; time effect; cohort effect; urban; China